Impact of staffing a surgical intermediate care unit with a critical care specialist - Géraldine Paratte; Tobias Zingg; Valérie Addor; Hélène Krief; Markus Schäfer; Nicolas Demartines (Swiss Medical Weekly, 2019)
AIM